Community of Mangrove Category Tree and Sapling in The Sekotong Bay, West Lombok - Lalu Japa; Karnan Karnan; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Community of mangrove in the Bay of Sekotong, West Lombok was studied to know the species composition, individual density of each species, and percentage covering of mangrove canopy. Total 28 plots of 10 m x 10 m were set in 9 transects in 5 stations. Photographs of canopy covering and mangrove community composition were analyzed by using software ImageJ and template spreadsheet 10x10, the new version of March 2018. The community of mangrove of Sekotong bay, West Lombok consists of 8 species, 5 genera, and 4 families. Rhizophora apiculata & Rhizophora stylosa were recorded in seven of nine transects (78% of transect).ÃÂ Ceriops tagal was a species that was also recorded to have the highest density (3700 trees/ha) in transect SKTM02B. The average density of the mangrove sapling category was higher than the mangrove tree category. The three highest covering percentages of canopi mangrove community took place in transects SKTM01A, SKTM01B, and SKTM04T.